Signifikansi Candi Tinggi dalam Sejarah dan Pelestarian Budaya Jambi - Nasrullah, Ahmad Fuad; Hidayatullah, Arif; Ardiansyah, M. Iqbal; Riyanto, M.; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
Candi Tinggi is an archaeological site located in Jambi, Indonesia, and is an important part of the cultural heritage of the Jambi Malay Kingdom which has a long history. This temple, which is estimated to date from the 7th to 9th centuries AD, is a silent witness to the development of Hindu-Buddhist culture in the Sumatra region. Research on Candi Tinggi not only focuses on archaeological and historical aspects, but also on its influence on the development of culture and identity of the Jambi community to this day. Candi Tinggi was built with a stone structure that is still clearly visible and has carvings that show Indian influences in its design and architecture, reflecting the relationship between the local kingdom and foreign cultures. This study aims to examine in depth the architectural structure, symbolism in the temple reliefs, and its historical context in relation to the Srivijaya Kingdom and surrounding kingdoms. Using qualitative research methods, this study collected data from primary sources in the form of direct observations at the location, as well as secondary data from relevant literature. The results of the study indicate that Candi Tinggi has great significance in the context of religion, politics, and culture during the heyday of Srivijaya. This discovery provides broader insight into Jambi's role as a center of trade and civilization in the past. In addition, this study also identified challenges in the preservation of Candi Tinggi, including threats from urbanization and lack of public awareness of the importance of the historical site. Therefore, more serious conservation efforts are needed to maintain this cultural heritage so that it can be enjoyed by future generations.